Systematic Review of the Epidemiology and Natural History of the Metabolic Vascular Syndrome and its Coincidence with Type 2 Diabetes Mellitus and Cardiovascular Diseases in Different European Countries - Kwasny, Caroline; Manuwald, Ulf; Kugler, Joachim; Rothe, Ulrike (Hormone and Metabolic Research, 2018)
The objectives of this systematic review were to estimate the incidence, prevalence and natural history of the metabolic (vascular) syndrome (MVS) among adults in different European countries. Furthermore, we assessed its co-incidence with type 2 diabetes (T2DM) and cardiovascular diseases (CVD). PubMed, MedLine, and EMBASE (via Ovid) were searched for relevant studies. After reading 116 full-text articles to find eligible ones, 66 publications met our inclusion criteria. Data for the incidence are based on a study from Portugal, in which the incidence rate for the MVS was 47.2/1000 person-years. Prevalence varied strongly depending on country and definition. The lowest was found in the United Kingdom (3%), the highest in Finland (71.7%). No article that deals with the natural history of the MVS was found. Considering the co-existence of MVS and T2DM, it ranged between 2% (United Kingdom) and 74.4% (Spain). The co-occurrence of MVS and CVD ranged from 2.8% (Italy) up to 52% (Netherlands). Coronary heart disease (CHD) varied between 1.2% and 44.2%. With regard to peripheral artery disease (PAD), values between 3.3% and 59.8% were found. Due to the many different definitions of the MVS, a comparison is very difficult. Overall prevalence ranged between 3% and 71.7% depending on definition, age, and country. An association between MVS and T2DM as well as several CVD can be assumed.
Keywords: metabolic syndrome; incidence; prevalence; clinical course; prediabetes